Twin-like defects in L10 ordered τ-MnAl-C studied by EBSD. (December 2015) - Bittner, F.; Schultz, L.; Woodcock, T.G.
Graphical abstract: Abstract: Twin-like defects in τ-MnAl-C, which has the L10 structure, have been studied using electron backscattered diffraction (EBSD) in as-transformed and in subsequently hot extruded samples. In both states, three distinct twin-like defects were found, whose misorientations were described by rotations of 62°, 118° and 180° about the normal to {1 1 1}. These are denoted as pseudo twins, order twins and true twins, respectively. The true twins are often observed in this type of material. The order twins formed the boundaries between regions where the c -axes were almost perpendicular to each other and these were thought to form due to the accumulation of strains during the transformation to τ from the hexagonal parent phase, ε. Due to symmetry, pseudo twins necessarily appeared at points where order twins interacted with true twins. The frequency of the different defects was very sensitive to the sample state. As the parent phase ε is not involved in the dynamic recrystallization which occurred during hot extrusion, there was a greatly reduced fraction of order twins and pseudo twins in the hot extruded state. The misorientation angle of the magnetically easy 〈0 0 1〉 axis across the three twin-like defects was 48°, 86° and 75° for pseudo, order and true twins, respectively. The interaction of the three twin-like defects with 180° magnetic domain walls and the resulting effect on the magnetic properties of the material may therefore be different.